Development of Construction Inventory Application with Rapid Application Development Method - Sihombing, Denny Jean Cross (Teknik Informatika Universitas Pamulang, 2023)
The construction industry plays a pivotal role in developing essential physical infrastructure and public facilities. Efficient inventory management is crucial for the growth and productivity of this industry. However, construction inventory management faces complex challenges due to the frequent project changes and coordination demands. Many construction companies still rely on manual processes or outdated software, leading to calculation errors, reporting delays, and an inability to swiftly adapt to project changes. To address these issues, this research introduces the Construction Inventory Application, developed using the Rapid Application Development (RAD) approach. This specialized application enhances construction inventory management by allowing rapid development, user involvement, early testing, and customization to meet unique project needs. The study demonstrates that the RAD-based Construction Inventory Application has the potential to significantly improve construction inventory management, minimizing risks associated with inefficiencies. This research contributes to advancing application development in the construction industry, aiding in efficient infrastructure development.